Сірето-Дністровська ділянка шляху доби пізньої та фінальної бронзи - Ільків, Микола (Колір ПРО, 2012)
The article provides reconstruction of the Siret-Dniester part of a road of the late and final stage of the Bronze Age based on the analysis of finds and localization of settlements. It ran along the rivers Dniester – Sovytsya/ Potichok – Prut – Derehluy – Siret. The nature of material is indicative of relations of the local population with Transylvania and the Lower Danube region.
The Siret-Dniester part of a road of the Late and Final Bronze Age
Keywords: Bronze Age; ancient road; Carpathian region